Effect of implant surface material and roughness to the susceptibility of primary gingival fibroblasts to inflammatory stimuli. Issue 6 (June 2020) - Andrukhov, Oleh; Behm, Christian; Blufstein, Alice; Wehner, Christian; Gahn, Johannes; Pippenger, Benjamin; Wagner, Raphael; Rausch-Fan, Xiaohui
Abstract: Objectives: The impact of the implant surface material and roughness on inflammatory processes in peri-implantitis is not entirely clear. Hence, we investigated how titanium and zirconia surfaces with different roughness influence the susceptibility of primary human gingival fibroblasts to different inflammatory stimuli. Methods: Primary human gingival fibroblasts were isolated from 8 healthy individuals and cultured on following surfaces: smooth titanium machined surface (TiM), smooth zirconia machined surface (ZrM), moderately rough titanium surface (SLA), or moderately rough zirconia surface (ZLA). Subsequently, stimulation with one of the following stimuli was performed: Porphyromonas gingivalis lipopolysaccharide (LPS), tumor necrosis factor (TNF)-α, interleukin (IL)-1β. The resulting production of IL-6, IL-8, and monocyte chemoattractant protein (MCP)-1 was measured by qPCR and ELISA. Results: P. gingivalis LPS induced IL-6 and MCP-1 production was slightly higher on titanium surfaces compared to zirconia surfaces. IL-1β induced IL-6 production was not affected by any surface characteristic. The production of MCP-1 in response to IL-1β was higher on smooth compared to rough surfaces and was not affected by the material. The production of IL-6 and MCP-1 in response to TNF-α was most strongly affected by surface characteristics. Higher production of these cytokine was observed on smooth compared to rough surfaces and on titanium compared to zirconia surfaces. Surface characteristics had only minor effects on IL-8 production. Significance: The susceptibility of primary gingival fibroblasts to inflammation depends on various factors, such as surface material, surface roughness and the nature of inflammatory stimuli. All these factors might determine susceptibility to peri-implantitis.